2015
DOI: 10.5965/223811711712018136
|View full text |Cite
|
Sign up to set email alerts
|

A qualidade de sementes de buva pode ser reduzida devido à resistência a glyphosate?

Abstract: The resistance to glyphosate may provide a penalty on plant growth and physiology. We investigate if the resistance to glyphosate reduces the seed quality of Conyza bonariensis by performing seed viability and vigor tests under a completely randomized design with four replicates of 50 seeds for both glyphosatesusceptible (S) and -resistant (R) biotypes. Low seed viability (<50%) was found in both S and R biotypes. No difference occurred between either S and R biotypes on seed germination and embryo viability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
1
1
Order By: Relevance
“…These results suggest that seeds of R biotypes deteriorate and die faster than seeds of S biotypes at high temperatures. These results are consistent with those observed by Costa et al [23] in C. bonariensis. At the vegetative level, there is no evidence for fitness cost in glyphosate-resistant Conyza species [5,26,28,37]; however, our results suggest that there may be a seed level fitness penalty in C. bonariensis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results suggest that seeds of R biotypes deteriorate and die faster than seeds of S biotypes at high temperatures. These results are consistent with those observed by Costa et al [23] in C. bonariensis. At the vegetative level, there is no evidence for fitness cost in glyphosate-resistant Conyza species [5,26,28,37]; however, our results suggest that there may be a seed level fitness penalty in C. bonariensis.…”
Section: Discussionsupporting
confidence: 94%
“…The viability of seeds was low (±50% or less) in relation to other studies that have reported viability rates between 65% and 80% in R and S Conyza populations [11,19]. However, there are also cases with lower germination rates [2,23]. This discrepancy in the viability and germination rates may be due to seed longevity; in the particular case of the Conyza species, longevity is short due to the small size of seeds resulting in few stored reserves [32]; therefore, it is normal to observe the deterioration or death of seeds [15].…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation